Psychiatry and transcendence - Healy, Jack (Journal of religion and health, 1995)
In the relationship which over the years has developed between psychiatry and religion, a common philosophical view of the human person has not always been in evidence. From a Catholic perspective this paper proposes a view which underscores the attribute oftranscendence in the person and accounts for that reality too often shunned by psychiatry, namely, a person'sspiritual life.